IMPROVING STUDENT LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF THE REASONING AND PROBLEM SOLVING (RPS) MODEL ON HUMAN RIGHTS MATERIALS IN CLASS XI MM 1 SMK NEGERI 1 DLANGGU MOJOKERTO - Rini Tugaswati (Jurnal Scientia, 2022)
Citizenship education subjects are subjects that focus on the formation of citizens who understand and are able to carry out their rights and obligations to become intelligent, skilled and characterized Indonesian citizens mandated by Pancasila and the 1945 Constitution. Initial observations at SMK Negeri 1 Dlanggu obtained daily test scores for class XI MM 1. More than 50% did not complete in learning. The number of students who have not completed is 12 students with a completeness percentage of 60%. Based on the description, it shows that the learning outcomes of human rights material do not reach the minimum completeness criteria. The low learning outcomes are due to the application of learning models that are not suitable, students are passive in learning, there is no assessment of assignments. The purpose of this study was to analyze the increase in learning outcomes for class XI MM 1 SMK Negeri 1 Dlanggu, through the application of the Reasoning And Problem Solving (RPS) learning model. To improve student learning outcomes on human rights material, a classroom action study was conducted which consisted of two cycles. Each cycle consists of stages of planning, implementation, observation and reflection. The subjects of this study were students of SMK Negeri 1 Dlanggu Class XI MM 1 academic year 2019/2020 which consisted of 28 students. The data collection instrument in this study was a matter of evaluation for the cognitive domain which was carried out at the end of each cycle. Based on the results and discussion, it can be concluded that learning using the Reasoning And Problem Solving (RPS) learning model provides convenience for teachers in learning, makes learning centered on students, completes learning outcomes, and can teach and train students' character behaviors. The implementation of the lesson plans was categorized as good with an average score of 3.0 in the first cycle and 3.27 in the second cycle. Student activity reached 85.26% in the first cycle and increased to 92.22%. In the aspect of scientific behavior, both cycles show that they are in the good category. Mastery learning outcomes also showed an increase, from 75% in the first cycle to 92.86% in the second cycle.